The Search for Truth through Eastern Symbolism: Spiritual Motives in the Literary Works of Timur Pulatov (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is dedicated to the exploration of spiritual motifs in the literary works of Timur Pulatov through the lens of Eastern symbolism. The paper analyzes how Eastern philosophical teachings (Buddhism, Sufism, Taoism) and their symbols, such as the path, river, desert, and bird, are reflected in the author's works. It examines how Pulatov uses these images to express the search for truth and self-discovery of his characters. The article sheds light on the philosophical and cultural roots of the writer's works, revealing their connection to Eastern thought and its influence on the form and content of the texts. The study emphasizes the importance of these symbols for understanding the inner world of the characters and their aspirations.